2014
DOI: 10.3390/s140203702
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Precision and Reliability of the Leap Motion Sensor and Its Suitability for Static and Dynamic Tracking

Abstract: We present the results of an evaluation of the performance of the Leap Motion Controller with the aid of a professional, high-precision, fast motion tracking system. A set of static and dynamic measurements was performed with different numbers of tracking objects and configurations. For the static measurements, a plastic arm model simulating a human arm was used. A set of 37 reference locations was selected to cover the controller's sensory space. For the dynamic measurements, a special V-shaped tool, consisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
189
2
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(207 citation statements)
references
References 10 publications
9
189
2
4
Order By: Relevance
“…This coincides with what has been reported by Guna and colleagues [33]. Guna et al [33] establish that "the results of the dynamic scenario revealed the inconsistent performance of the controller, with a significant drop in accuracy for samples taken more than 250mm above the controller's surface.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This coincides with what has been reported by Guna and colleagues [33]. Guna et al [33] establish that "the results of the dynamic scenario revealed the inconsistent performance of the controller, with a significant drop in accuracy for samples taken more than 250mm above the controller's surface.…”
Section: Discussionsupporting
confidence: 76%
“…Kowalczewski and Prochazka [21], and Colombo et al [31] establish therapy abandonment as one of the main problems in the motor rehabilitation process. For this reason, our main goal in this research is to determine the mental workload and performance of patients while they perform their motor hand therapy using a low cost robotic device (Novint Falcon haptic device [32]) and a (non-robotic) gesture sensor (Leap Motion Controller [33], [34]). This paper is structured as follows.…”
Section: Introductionmentioning
confidence: 99%
“…As stated in Ref. [22], the measurement noise for a static marker is given by its standard deviation for each individual coordinate: SD X = 0.018 mm, SD y = 0.016 mm, and SD z = 0.029 mm. In view of the given results, we can regard the measurement inaccuracy of the reference system as negligibly small.…”
Section: Optical Tracking Systemmentioning
confidence: 99%
“…This class tends to be unreliable in highly dynamic environments, limited in range and expensive [29]. 4.…”
Section: Data Acquisition Through Object Trackingmentioning
confidence: 99%